Temporal analog of Fabry-Pérot resonator via coherent population trapping - Ruihuan Fang (Nature Portfolio, 2021)
Abstract Ramsey spectroscopy via coherent population trapping (CPT) is essential in precision measurements. The conventional CPT-Ramsey fringes contain numbers of almost identical oscillations and so that it is difficult to identify the central fringe. Here we experimentally demonstrate a temporal analog of Fabry–Pérot resonator via double-Λ CPT of laser-cooled 87Rb atoms. By inserting a periodic CPT pulse train between the two CPT-Ramsey pulses, due to the constructive interference of spin coherence, the transmission spectrum appears as a comb of equidistant peaks in frequency domain and thus the central Ramsey fringe can be easily identified. From the five-level Bloch equations for our double-Λ system, we find that the multi-pulse CPT interference can be regarded as a temporal analog of Fabry–Pérot resonator. Because of the small amplitude difference between the two Landé g factors, each peak splits into two when the external magnetic field is not too weak. This splitting is exactly linear with the magnetic field strength and thus can be used for measuring a magnetic field without involving magneto-sensitive transitions.